EVALUASI MANAJEMEN PEMBINAAN OLAHRAGA ATLETIK DI KLUB ATLETIK PANDAAN KABUPATEN PASURUAN (Arena, 2012)
Abstract One of the factors that must considered in build and develops an sport organization is management, with good management, so it will help the achievement improvement that effective and efficient. The development of athletic sports branch on Pasuruan district can be said well, since the existence of Pandaan athletic club on Pasuruan district. Whereas this organization is a place to develop on of sport branch namely athletic and expected to develop successful athlete that have achievement on regional, national or international stage. So it can help the achievement progress on Pengcab PASI Kabuaten Pasuruan. Research results are 1) The talented athlete scouting done by execute 5k and 10k competition on elementary school, junior high school and senior high school student and to recruit coach based on their experiences. 2) The development and condition of Pandaan athletic club at Pasuruan distric have run well. 3) the completion of infrastructure still lack, it proved the absence of facility of jump field. 4) Training program that gave by Pandaan athletic club coach at Pasuruan district based on athlete capacity. 5) Once of a month execute try out with purpose to measure athlete capability so far, during they following development on Pandaan athletic club at Pasuruan district. Fund that come from KONI every six month still lack maximal. Several infrastructure facilities that need to receive improvement and addition is special training place of athletic sport branch. Conclusion: 1) athlete recruitment is running well and doing properly, so that it will need to execute various games from elementary school, junior high school and senior high school stages. In recruiting coach also already done well since in recruiting process by following coaching training and also based on experiences. 2) Tasks and leadership on Pandaan athletic club at Pasuruan district handled by Amir Hamzah with advisor Amang Mulahela. 3) Infrastructure in Pandaan athletic club at Pasuruan district can be said still incomplete if compared with other East Java clubs such Surabaya, Malang, Blitar and Kediri. 4) The quality if coach on Pandaan athletic club at Pasuruan district is good enough, with the application of good training program, it proved from the athlete achievement improvement. 5) to measure athlete capability during development have done well, it proved that once of a month execute try out. 6) Administration system on Pandaan athletic club at Pasuruan district can be said well enough. Operational fund resource comes from KONI that paid every six month. Keywords: evaluation, management, Pandaan athletic club, Pasuruan distric